Persulfate-based controlled release beads for in situ chemical oxidation of common organic pollutants. Issue 5 (October 2021) - Ma, Jie; Ma, Yao; Rong, Xun; Song, Quanwei; Wu, Baichun; Lan, Xingying; Feng, Yuan; Qiu, Xiaoyuan; Zhang, Ping
Abstract: Groundwater contamination by organic pollutants is a growing threat to the environment and human health. As a cost-effective method, in situ chemical oxidation (ISCO) treatment has become a popular technical method to degrade groundwater pollutants. However, conventional ISCO treatment can suffer from a number of operational issues, such as tailing and concentration rebound, and thus the long-term treatment effectiveness is less desirable. As an alternative approach to the conventional ISCO method, controlled release materials are designated to gradually release oxidant chemicals to treat polluted groundwater with an extended chemical release duration and a reduced peak release rate. In this study, novel persulfate-paraffin based controlled release bead (CRB) materials were prepared and tested in a laboratory setting for their applicability in groundwater organic pollution remediation. It shows that bead size and temperature can substantially affect the release kinetics of persulfate from the CRBs, while the impact of solution pH and the presence of matrix anions are insignificant. Moreover, degradation experiments of benzene, toluene, ethylbenzene, and xylene pollutants show that the performance of CRBs, particularly within a short period after being delivered in situ, is on par with the conventional ISCO method using aqueous persulfate. This study expands our understanding and capacity in adopting controlled release materials for groundwater remediation. This study promotes the potential field application of such novel controlled release materials for environmental remediation of groundwater. Graphical Abstract: ga1 Highlights: Prepare persulfate-based controlled release bead (CRB) for groundwater remediation. Persulfate (PS)-paraffin CRBs can release PS in a controlled and sustained manner. Temperature can strongly impact the release of PS from PS-paraffin CRBs. PS-paraffin CRBs demonstrate a desirable performance in degrading organics. PS-cement CRBs have a rapid release kinetics with a reduced release lifetime.